A hurdle approach of acidic electrolyzed water simultaneous with ultrasound to inactivate Bacillus cereus. Issue 10 (13th August 2019) - Lv, Ruiling; Mingming, Zou; Chen, Weijun; Wang, Danli; Zhou, Jianwei; Ding, Tian; Ye, Xingqian; Liu, Donghong
Abstract: This study evaluated the inactivation effect of the ultrasonic treatment combined with acidic electrolyzed water (AEW) on Bacillus cereus . Ultrasound treatment for 10 min induced 0.69 log CFU/ml reduction of B. cereus in sterile saline, while AEW treatment resulted in 1.05 log CFU/ml for the same time. Simultaneous ultrasound and AEW treatment reduced 1.98 log CFU/mL which had synergistic effect for 10 min at 20°C. Flow cytometry combined PI/cFDA and electron microscope were applied to investigate the inactivation mechanisms. Ultrasound inactivated B. cereus by thinning cell wall, forming pores, damaging structure and so on. However, there was no sublethal injured cells after ultrasound treatment, indicating it was an all‐or‐nothing process. AEW mainly affected the esterase activity with relatively intact cell structure. More strikingly, simultaneous ultrasound and AEW did remarkable impact on the structure. Practical applications: Ultrasound is a green non‐thermal technique and has widely use in food industry. Also, electrolyzed water is an effective and broad‐spectrum sanitizer which is environmentally friendly and cost‐effective. The results of the study indicated that simultaneous ultrasound and acidic electrolyzed water treatment had significant inactivation effect on Bacillus cereus, it would be a promising method which was effective, short time‐consuming, and green.